An analysis of thixotropic micropore variation and its mechanism in loess - Wei, Le; Dang, Faning; Ding, Jiulong; Wu, Xiaojuan; Li, Jiayang; Cao, Zhengzheng (Frontiers in Ecology and Evolution, 2023)
The relationship between the thixotropic mechanism and the macroscopic thixotropic strength can be clarified by analyzing the changes in microstructure and pores in the loess thixotropic process. This approach is of significant importance for calculating the strength of compacted loess foundations. In the present study, a representative sample prepared from Xi'an loess was analyzed and eight resting ages were set. The micropore characteristics of the remolded loess and undisturbed loess at different resting ages were obtained using electron microscope observation and nuclear magnetic resonance testing. The results indicate that the thixotropy in the prepared loess samples is significant. It is also found that as the resting age grew, newly formed cements in the remolded loess continuously accumulated and filled in the microcracks between the aggregates. Consequently, the contact area of aggregates increased, thereby decreasing the width and length of the microcracks. The proportion of cementation pore and small microcracks gradually increased, while the proportion of large microcracks gradually decreased, indicating that thixotropy increased the cohesive force and friction force of soil structure at the mesoscale. This phenomenon also explains the increase of thixotropic strength at the macroscopic scale. The mesoscopic mechanism of loess thixotropic strength recovery is that the connection between soil particles is re-established after the break of the clay particle-watercharge system. Moreover, the elastic potential energy of soil particles generated by compression promoted the polymerization of clay particles dispersed in a pore water solution to produce flocculating aggregates during resting dissipation. The continuous consumption of clay particles expanded the processing time and flocs and 2 continuously decreased the strength growth rate.